Left-sided gall bladder found incidentally during emergency laparoscopic appendectomy due to acute appendicitis - Janež, Jurij (International Journal of Research in Medical Sciences, 2017)
The gallbladder is affected by a large number of congenital anomalies, which may affect its location, number, size, or form. Some of these malformations are very rare and may lead to misdiagnosis. Knowledge of the location of the gallbladder is of great importance for the surgeon, particularly when cholecystectomy or other biliary surgery is to be performed. There are many variants not only of the position of the gallbladder but also in the way the cystic duct joins the biliary tree. The left-sided gallbladder remains a scarce anomaly with prevalence of 0.3%. This report presents a case of a young male patient, who was operated due to acute appendicitis. Laparoscopic appendectomy was performed and at laparoscopy a left-sided gallbladder was found, located on the III liver segment, on the left side of the round ligament.